Urotensin Inhibition with Palosuran Could Be a Promising Alternative in Pulmonary Arterial Hypertension - Onat, Ahmet Mesut; Pehlivan, Yavuz; Turkbeyler, Ibrahim Halil; Demir, Tuncer; Kaplan, Davut Sinan; Ceribasi, Ali Osman; Kisacik, Bunyamin (Springer/Plenum Publishers, 2013)
Pulmonary arterial hypertension (PAH) is a progressive and a life-threatening disease with its high morbidity and mortality ratios. On searching for new shining targets in pathogenesis, we noticed, in our previous studies, urotensin-II (UII) in systemic sclerosis with potent angiogenic and pro-fibrotic features. Owing to the mimicking properties of UII with endothelin-1 (ET1), we attempted to investigate the effect of palosuran in a PAH rat model. Thirty rats were randomly divided into three groups, with each group comprising 10 rats: group 1 (control group) received the vehicle subcutaneously, instead of monocrotaline (MCT) and vehicle; group 2 (MCT group) received subcutaneous MCT and vehicle; and group 3 (MCT + palosuran group) received subcutaneous MCT and palosuran. Serum UII, ET1, transforming growth factor-beta 1 (TGF-beta 1) levels, pulmonary arteriolar pathology of different diameter vessels, and cardiac indices were evaluated. The ET1, TGF-beta 1, and UII levels were significantly diminished in the treatment group, similar to the controls (p < 0.001). Right ventricular hypertrophy index and mean pulmonary arterial pressure scores were also significantly reduced in the treatment group (p = 0.001). Finally, in the 50-125-mu m diameter arterioles, in contrast to Groups 3 and 1, there was a statistically significant thickness (p < 0.01) in the arteriolar walls of rats in Group 2. The treatment effect on arteries of more than 125-mu m diameters was found to be valuable but not significant. Owing to its healing effect on hemodynamic, histological, and biochemical parameters of MCT-induced PAH, palosuran as an antagonist of UII might be an optional treatment alternative for PAH.
Keywords: pulmonary arterial hypertension (PAH); urotensin-II antagonist; palosuran